Growth Performance and Cost Benefits of Broilers Fed Diets Containing Ipomoea asarifolia Leaf Meal - Ugwuowo Chidi Leonard; Osita Onochie Charles; Ezeano Ike Caleb; Chukwkuka Chiemelie Esther (Jurnal Ilmu Ternak dan Veteriner, 2022)
This experiment was conducted to determine growth performance and cost benefit of including cooked Ipomoea asarifolia leaf meal (CIALM) in broiler diets. Eight diets were compounded by including Ipomoea asarifolia leaf meal at 0, 2.5, 5 and 7.5% to form T1, T2, T3 and T4 respectively of both starter and finisher diets. One hundred and twenty broiler birds were used in a Complete Randomized Design experiment that lasted for eight weeks.  Daily feed intake and weekly weight gain were measured. Average daily feed intake, average daily weight gain, total feed consumed, feed conversion ratio and cost benefit parameters were calculated. In starter phase results showed that there were significant differences (P0.05) between treatment means in all the parameters except initial weight of the birds. There were significant differences (p0.05) between treatment means in all the parameters measured during the finisher phase including the cost analysis parameters except that feed cost decreasing with increasing levels of CIALM and net profit decreased from T1 to T4 because of the decrease in total weight gain from T1 to T4. Final weight gain, total weight gain, average daily feed intake, total feed intake, average daily weight gain, feed conversion ratio, feed cost and feed cost per kg weight gain all decreased with increasing levels of CIALM. Results control diet performed better than other treatment diets which suggest that lower levels of inclusion that is less than 2.5% may give positive results.